Language as a Mirror of Cultural Identity: A Stylistic Analysis of Arabic Poetry by Mahmoud Darwish - Rayhan Muhamad Ridwan; Ade Nandang; Astri Khodimatus Sholihah; Riskiyatul Hasanah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study is intended to examine the poems of Mahmoud Darwish through a stylistic approach in order to reveal the relationship between language, culture, and identity within the context of the Palestinian nation’s non-violent struggle. Mahmoud Darwish, as the national poet of Palestine, uses language not merely as an aesthetic medium but also as a symbol of cultural resistance and as an expression of the people’s collective identity. This research is a qualitative study employing library research methods, analyzing stylistic elements and the complexity of linguistic symbols that represent culture in poems integrating aesthetics and politics. It contributes to understanding the use of language style as a medium of cultural resistance and as a reflection of Palestinian identity, expanding the comprehension of the interconnection among language, culture, and struggle within the framework of literature. The findings show that Mahmoud Darwish’s poems are rich in metaphorical, symbolic, and repetitive language styles that reinforce messages of alienation, longing for the homeland, and broader depictions of resistance against colonization. The analysis indicates that the use of language in Darwish’s poetry functions strategically as a tool of non-violent resistance that fosters collective awareness and strengthens Palestinian national identity amid social and political pressures. Thus, Mahmoud Darwish’s poetry possesses not only literary aesthetic value but also serves as an effective instrument of cultural resistance.